Metabolic Profile and Adipokine Levels in Overweight and Obese Dogs - De Marchi, Paula Nassar [UNESP]; Machado, Luiz Henrique De Araújo [UNESP]; Holsback, Luciane; Ragazzi, Jéssica Calesso; Fagnani, Rafael; Júnior, Ademir Zacarias; Zahn, Fabíola Soares [UNESP]; Cardoso, Mauro José Lahm (My University, 2021)
Obesity in dogs is increasingly present in the veterinary practice. In humans, it’s known that there is a significant correlation between obesity and the development of hypertension and insulin resistance, a clinical picture called metabolic syndrome. In dogs, however, there is only anecdotal about it. The objectives of the study were1 to determine serum levels of adiponectin, leptin, triglycerides, cholesterol, insulin, glucose, HOMA-B, HOMA-IR, and systolic blood pressure in dogs with different body conditions (BC) without endocrine disease. Seventy six healthy dogs submitted to evaluation of BC and morphometry. The dogs were separated into four groups: Optimal BC (ECC 3,4 or 5 of 9 and GC% of 13 to 27-G1), overweight (ECC 6 and 7 of 9 and GC% of 14 to 38- G2), obese (ECC 8 and 9 of 9 and GC% greater than or equal to 34-G3). G3 presented higher serum levels of total protein, triglycerides, glucose, insulin, and HOMA-IR. Adipokines didn’t correlate to any other parameter, but the occurrence of hyperinsulinemia was higher in G3. The results have shown that obese dogs presented IR and alterations in fat metabolism.
Keywords: Adipokines; Insulin Resistance; Obesity; Systolic Hypertension